Strain and crack analysis within concrete members using distributed fibre optic sensors. (November 2019) - Sieńko, Rafał; Zych, Mariusz; Bednarski, Łukasz; Howiacki, Tomasz
This article presents laboratory tests, with the purpose being to verify the suitability of standard optical fibres in a tight jacket for advanced strain analysis within concrete members. An optical reflectometer was used to enable the optical signal to be processed on the basis of the Rayleigh scattering phenomenon, so that strains and/or temperature changes were determined along the length of the measuring fibre. The measurements were carried out continuously in a geometrical sense (distributed measurements), with a spatial resolution starting from as fine as 5 mm. The arrangement of optical fibres inside the heterogeneous concrete medium and on its surface allowed for the identification and detailed analysis of local phenomena such as cracks. Remote and early location of structural damage with an estimation of its scale provides new opportunities for the monitoring of the structural health of reinforced concrete structures, facilitating the interpretation of its behaviour as well as failure risk management based on comprehensive and reliable measurement data. If traditional spot techniques are used, this approach is not possible. The aim of the initial studies was to analyse the strain distributions over compressed and tensioned measurement sections located on the surface of a cylindrical specimen of concrete. In the tests which followed, the reinforced concrete rod was eccentrically tensioned with fibre optics installed inside. Qualitative and quantitative verification of crack widths was made, with a narrow range up to 0.05 mm and a wider one to 0.30 mm. The results of the studies show very good accuracy of optical fibre sensor technology as a reference technique during the analysis of microcracks and narrow cracks, and moderate accuracy in the case of wider cracks. Despite using optical fibres in a tight jacket which mediates in strain transfer, the results obtained can be very suitable for the assessment of the structural condition of the member under consideration. It is also worth noting that the tests conducted indicate the effectiveness of distributed optical fibre technology for the analysis of concrete homogeneity and its structural behaviour within compressed areas, as it is possible to calculate strains over measuring bases that start from lengths as short as 5 mm.